Respiratory and infectious complications of premature neonates of pregnant mothers with disease during pregnancy and compare with healthy mothers - Hasan Boskabadi; Nafiseh Pourbadakhshan (Mashhad University of Medical Sciences, 2022)
Introduction: Maternal diseases during pregnancy have many effects on the fetus and infant, and on the other hand, respiratory and infectious problems are very common in premature neonates, so this study was performed with aim to compare these two common problems in mothers with normal and problematic pregnancies. Methods: In this retrospective descriptive study, the premature neonates hospitalized in the NICU of Ghaem Hospital, Mashhad during 2014-2022 were examined, and the information related to the study, including maternal information (mother's age, type of delivery, maternal diseases  and pregnancy complications) and newborn information (respiratory problems, blood culture, complete blood cell count, C-reactive protein(CRP) and Erythrocyte Sedimentation Rate ( ESR)) were recorded. Then the neonates' characteristics in the two groups of healthy mothers and mothers with common pregnancy diseases were compared. Data were analyzed by SPSS (version 26) and Independent t-test and Chi-square test. P<0.05 was considered statistically significant. Results: From a total of 982 mothers and newborns, mean gestational age in the group of healthy and diseased mothers was 31.93 and 30.95 weeks, the incidence of respiratory distress syndrome was reported in 39 (32.5%) and 357 infants (56.9%), non-specific respiratory distress in 13 (7.8%) and 105 infants (12.9%), primary pulmonary hypertension in 0 and 22 infants (2.7%), sepsis in 37 (22.4%) and 219 infants (26.8%), and the incidence of meningitis in 2 (1.2% ) and 15 infants (1.8%), respectively (P<0.001) Conclusion: Prematurity, its severity and related problems increase in infant of mothers with problems during pregnancy. Respiratory and infectious problem, respiratory support and necessary care also increase.